Literature Review: Media Pembelajaran Berbasis Artificial Intelligence terhadap Efektivitas Belajar Siswa - Wina Dhamayanti; Henni Kunatan (STAB Kertarajasa, 2026)
The development of Artificial Intelligence (AI) technology has significantly influenced the field of education, particularly in the use of interactive learning media. This study aims to analyze the effectiveness of AI-based learning media on students’ learning outcomes using a literature review method. Data were obtained from various journals and previous studies discussing the implementation of AI in education. The findings indicate that AI is effective as a learning medium because it can improve learning motivation, student skills, teacher competence, and the overall quality of the learning process. Various AI-based media such as Canva AI, AI interactive videos, AI Puzzle Maker, AI-assisted 3D animation videos, and AI-based digital learning platforms have proven to create more interactive, personalized, adaptive, and engaging learning experiences. In addition to improving learning outcomes, AI also helps teachers prepare learning materials more effectively and efficiently. However, the implementation of AI still faces several challenges, including limited infrastructure, low digital literacy among teachers, ethical and privacy concerns, and unequal access to technology. Therefore, educational policy support, infrastructure improvement, and AI training for educators are needed to optimize the implementation of AI in learning.